Determination of the real exchange rate in commodity exporting countries: do commodity prices matter? - Sitole, Risenga Wiseman (My University, 2017)
This study examines the relationship between major commodity exports and the real exchange rate of commodity exporting countries. We make use of monthly commodity price time series data to determine the causality relationship between exchange rates and the top three commodity exports from 5 commodity exporting countries (Brazil, Chile, Mexico, Norway and South Africa). Due to the phenomenon called “Dutch Disease” commodity exporting countries’ economies are found not to experience large economic success during periods of booming export commodity prices. Using data from the IMF IFS database, only one country out of the five included in this study shows evidence of conitegration relationship between commodity prices and exchange rates, although there is some evidence of commodity prices explaining the movement of exchange rates in all five countries. We find that commodity prices do play a role in the exchange rates movement in commodity exporting countries.
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2017.
Keywords: Commercial products; Exports; International trade; Foreign exchange rates